2007
DOI: 10.2466/pms.104.2.467-480
|View full text |Cite
|
Sign up to set email alerts
|

Display Polarity, Stimulus Exposure Duration, and Visual Lobe Shape

Abstract: This study investigated the effects of visual display polarity and stimulus exposure duration on visual lobe shape. Analysis showed that regardless of display polarity and exposure duration combinations tested here, visual lobe contours were slightly irregular and asymmetric, of medium roundness, with a moderately rough boundary, and horizontally elongated with a mean length-width ratio of 1.53. Visual lobes mapped with negative display polarity were significantly rounder, slightly more regular and more symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In fact, the results are in accordance with the finding of Bauer and Cavonius (1980) that positive polarity can enhance sensitivity in contrast, speed of lens accommodation and reduce optical distortion, all of which are essential for better performance with the visual lobe mapping task. Chiu and Chan (2007) conducted a visual lobe mapping experiment on display polarity without variation of luminance or luminance contrast and found that visual lobe characteristics mapped under negative polarity was superior to that mapped under positive polarity. The contrast level used by them was 13:1 which is close to the low contrast level of 5:1 in this study.…”
Section: Display Polaritymentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the results are in accordance with the finding of Bauer and Cavonius (1980) that positive polarity can enhance sensitivity in contrast, speed of lens accommodation and reduce optical distortion, all of which are essential for better performance with the visual lobe mapping task. Chiu and Chan (2007) conducted a visual lobe mapping experiment on display polarity without variation of luminance or luminance contrast and found that visual lobe characteristics mapped under negative polarity was superior to that mapped under positive polarity. The contrast level used by them was 13:1 which is close to the low contrast level of 5:1 in this study.…”
Section: Display Polaritymentioning
confidence: 98%
“…Work on defining the optimum time to spend on inspection has been a major theme in visual search research for the past forty years (Krendel and Wodinsky 1960, Bloomfield 1973, Morawski et al 1980, Chan and Chan 2000, Chan and Yu 2010. Visual search has often been modeled as a sequence of fixations or glimpses so that the visual lobe of the person is moved around to cover the search area until a fault is detected (Chiu and Chan 2007, Repperger et al 2007, Gallwey 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Taptagaporn and Saito (1990) also recommended negative-polarity displays for dark environments based on changes in pupil diameter as an indicator of possible visual fatigue. Chiu and Chan (2007) further examined the visual lobe (visual contour) shape under different display polarities and stimulus exposure durations. In general, visual lobes have been described as roughly oval, with the horizontal axis longer than the vertical one.…”
Section: Display Polaritymentioning
confidence: 99%
“…Some recent studies have investigated the changes in visual lobe shape for different task conditions. Chiu and Chan (2007) found that visual lobes mapped with negative display polarity were significantly rounder than those mapped with positive polarity. When stimulus exposure duration increased from 200 to 400 ms, there were significant increases in the visual lobe area, perimeter, roundness, boundary smoothness, and regularity.…”
Section: Introductionmentioning
confidence: 99%